Abnormal Cerebral Blood Flow and Volumetric Brain Morphometry in Patients With Obstructive Sleep Apnea - Xiao, Ping; Hua, Kelei; Chen, Feng; Yin, Yi; Wang, Jurong; Fu, Xiangjun; Yang, Jiasheng; Liu, Qingfeng; Chan, Queenie; Jiang, Guihua (Frontiers in Neuroscience, 2022)
Obstructive sleep apnea (OSA) is a serious breathing disorder, leading to myocardial infarction, high blood pressure, and stroke. Brain morphological changes have been widely reported in patients with OSA. The pathophysiological mechanisms of cerebral blood flow (CBF) changes associated with OSA are not clear. In this study, 20 patients with OSA and 36 healthy controls (HCs) were recruited, and then pseudo-continuous arterial spin labeling (pCASL) and voxel-based morphometry (VBM) methods were utilized to explore blood perfusion and morphological changes in the patients with OSA. Compared with the HC group, the OSA group showed increased CBF values in the right medial prefrontal cortex (mPFC), left precentral gyrus, and right insula and showed decreased CBF values in the right temporal pole (TP) and the right cerebellum_Crus2. Compared with the HC group, the patients with OSA showed decreased gray matter volume (GMV) in the right dorsal lateral prefrontal cortex (DLPFC), the right occipital pole, and the vermis. There were no significantly increased GMV brain regions found in patients with OSA. Pearson correlation analysis showed that the reduced GMV in the right DLPFC and the right occipital pole was both positively correlated with Mini-Mental State Examination (MMSE) (r = 0.755, p < 0.001; r = 0.686, p = 0.002) and Montreal Cognitive Assessment (MoCA) scores (r = 0.716, p = 0.001; r = 0.601, p = 0.008), and the reduced GMV in the right occipital pole was negatively correlated with duration of illness (r = −0.497, p = 0.036). Patients with OSA have abnormal blood perfusion metabolism and morphological changes in brain regions including the frontal lobe and the cerebellum and were closely related to abnormal behavior, psychology, and cognitive function, which play an important role in the pathophysiological mechanism of OSA.